Peran Orang Tua Tunggal (Ibu) Dalam Melaksanakan Pendidikan Islam (Studi Kasus di Kenagarian Sago Salido Kecamatan IV Jurai) - Fitria, Weni - (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2024)
The thesis entitled "The Role of Single Parents (Mothers) in Implementing Islamic Education (Case Study in Kenagarian Sago Salido District IV Jurai)". Written by Weni Fitria, Nim 1372526 Islamic Education Study Program, Postgraduate Program at West Sumatra Muhamadiyah University. Education is placed as something important in human life. Through education the values of Islamic teachings can be delivered at once and applied in human life. Education and family life are two existential things that are directly involved in human life in the world. The role of both parents is very necessary in every development of life and implementing Islamic education for their children. But sometimes in a family there is only a single parent (mother) who raises and educates their children without being accompanied by a husband. For this reason, this study aims to find out how the role of Single Parents (Mother) in Implementing Islamic Education (Case Study in Kenagarian Sago Salido District IV Jurai) ". This study used a descriptive qualitative approach with a single parent research subject, a child from a single parent family. The data collection techniques used are observation, interviews and documentation. While the data analysis uses a qualitative data analysis model. The results of the study show that: 1. Single Parents in Kenagarian Sago Salido in general have carried out the duties and responsibilities of raising children, carrying out Islamic education. This can be seen from the implementation of children's education and the understanding and practice of Islamic teachings properly. But there are still single parents (mothers) who have not been able to carry out their duties and responsibilities. 2. The role of single parents is very large in carrying out Islamic education at the Kenagarian Sago Salido. Single parents (mothers) play a role in educating children and are directly involved in implementing Islamic education. Single parents (mothers) play a role in continuing children's education and instilling religious teaching values from an early age. 3. Single parents (mothers) at Kenagarian Sago Salido experience obstacles and challenges in implementing Islamic education for children. The biggest obstacle for single parents is economic limitations, and the absence of family leaders. While other obstacles to losing a father figure as a family leader, sadness left by a father figure and the influence of environmental relations on children even though that is not the biggest obstacle felt by single parents (mother). In overcoming all the obstacles and challenges, single parents (mothers) at Kenagarian Sago Salido have tried to work, in collaboration with the closest family to carry out children's education. In addition, the participation of the community and the government is also needed in overcoming these obstacles.